No Crystal Stair: Predictors of Pessimism Among Black Men. Issue 2 (June 2021) - Palmer, Gordon J. M.; Cole-Lewis, Yasmin C.; Goodwill, Janelle R.; Mattis, Jacqueline S.
Social scientists have paid scant attention to factors relating to pessimism among Black American men. Drawing from Fankl's existentialist framework, this study explored the association between life stress, everyday racism, existential well-being (EWB), religiosity and self-reported pessimism among a community sample of Black men ( n  = 147). Regression analysis revealed that life stress was positively associated with pessimism, while EWB was negatively associated with pessimism. Relative weights analysis indicated that EWB had the greatest explanatory power in the model. Findings suggest that future studies of pessimism among Black American men should account for men's sense of purpose and life stress, while also considering the potentially moderating effects of chronic and acute life stress on men's future orientation.